2011
DOI: 10.1021/es201212r
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Is Increasing in the Coastal Zone of the Baltic Sea

Abstract: Hypoxia is a well-described phenomenon in the offshore waters of the Baltic Sea with both the spatial extent and intensity of hypoxia known to have increased due to anthropogenic eutrophication, however, an unknown amount of hypoxia is present in the coastal zone. Here we report on the widespread unprecedented occurrence of hypoxia across the coastal zone of the Baltic Sea. We have identified 115 sites that have experienced hypoxia during the period 1955–2009 increasing the global total to ca. 500 sites, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
277
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(283 citation statements)
references
References 26 publications
6
277
0
Order By: Relevance
“…As a consequence of eutrophication, environmental problems like spreading of hypoxia and increased frequency and intensity of cyanobacteria blooms have been observed (Vahtera et al 2007). Hypoxia increased both in the deep offshore waters (Conley et al 2009;Savchuk 2010) and in the coastal zone (Conley et al 2011). …”
Section: Introduction the Baltic Sea Environmentmentioning
confidence: 97%
“…As a consequence of eutrophication, environmental problems like spreading of hypoxia and increased frequency and intensity of cyanobacteria blooms have been observed (Vahtera et al 2007). Hypoxia increased both in the deep offshore waters (Conley et al 2009;Savchuk 2010) and in the coastal zone (Conley et al 2011). …”
Section: Introduction the Baltic Sea Environmentmentioning
confidence: 97%
“…Even though major nutrient reduction strategies have been agreed to for the Baltic Sea catchment area, hypoxia has further expanded over the past 10 years and now affects both central basins and the coastal zone Conley et al 2011). Recently it has been suggested that the reduction of nutrient levels alone may not be able to neutralize or reverse the impact of eutrophication (Duarte et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The limited water exchange and the relatively large watershed makes the Baltic Sea vulnerable to eutrophication and increasing nutrient loads over several decades have increased the area, volume and frequency of oxygen deficiency not only in the deeper basins but also in the coastal areas (Nausch et al, 1999;Conley et al, 2011;Voss et al, 2011). The nitrogen part of the eutrophication is to some degree counteracted by removal of fixed nitrogen in the anoxic parts of sediments and water columns (Voss et al, 2005).…”
Section: Introductionmentioning
confidence: 99%